Effect of text messaging on memory recall among university students / Mohamad Azlan Mohamad Shah - Mohamad Shah, Mohamad Azlan (2018)
In this modern era, technology has become an absolute dependable medium, and it has enabled communication to be accessible everywhere, to everyone, without excluding students. Most of the devices are portable and capable of anything including texting. Many researchers have questioned the influence of this technology on people and the students, thus making it a great thing to be discovered. Text messaging has been a popular form of communication among university students. The purpose of this study is to examine the various conditions of text messaging and determine which condition is the most distracting for university students. Participants were randomly assigned to the control group, the receiving group, or the reply group. The result revealed that participants who were engaged in text messaging demonstrated significantly poorer performance on a test conducted compared with the group that did not reply or received text messages. This is because texting brought a classroom lecture with rivalry for the same cognitive source, therefore blocked the fundamental intellectual compositions. From this point of view, there will be a transitory decrement in execution while the university students are changing from the lecture to mobile contents and the other way around.